CYP2B6 SNPs are associated with methadone dose required for effective treatment of opioid addiction. (25th July 2011) - Levran, Orna; Peles, Einat; Hamon, Sara; Randesi, Matthew; Adelson, Miriam; Kreek, Mary Jeanne
ABSTRACT Adequate methadone dosing in methadone maintenance treatment (MMT) for opioid addiction is critical for therapeutic success. One of the challenges in dose determination is the inter‐individual variability in dose‐response. Methadone metabolism is attributed primarily to cytochrome P450 enzymes CYP3A4, CYP2B6 and CYP2D6. The CYP2B6*6 allele [single nucleotide polymorphisms (SNPs) 785A>G (rs2279343) and 516G>T (rs3745274)] was associated with slow methadone metabolism. To explore the effects of CYP2B6*6 allele on methadone dose requirement, it was genotyped in a well‐characterized sample of 74 Israeli former heroin addicts in MMT. The sample is primarily of Middle Eastern/European ancestry, based on ancestry informative markers (AIMs). Only patients with no major co‐medication that may affect methadone metabolism were included. The stabilizing daily methadone dose in this sample ranges between 13 and 260 mg (mean 140 ± 52 mg). The mean methadone doses required by subjects homozygous for the variant alleles of the CYP2B6 SNPs 785A>G and 516G>T (88, 96 mg, respectively) were significantly lower than those of the heterozygotes (133, 129 mg, respectively) and the non‐carriers (150, 151 mg, respectively) (nominal P = 0.012, 0.048, respectively). The results remain significant after controlling for age, sex and the ABCB1 SNP 1236C>T (rs1128503), which was previously shown to be associated with high methadone dose requirement in this population (P = 0.006, 0.030, respectively). An additional 77 CYP2B6, CYP3A4 and CYP2D6 SNPs were genotyped. Of these, 24 SNPs were polymorphic and none showed significant association with methadone dose. Further studies are necessary to replicate these preliminary findings in additional subjects and other populations.